2009
DOI: 10.1080/02652030802641898
|View full text |Cite
|
Sign up to set email alerts
|

Formation of styrene during the Maillard reaction is negligible

Abstract: The elucidation of chemical pathways and the identification of intermediates leading to vinylogous compounds such as acrylamide by the Maillard reaction have proven challenging. This study was conducted to assess the formation of styrene from L-phenylalanine, employing binary mixtures of the amino acid heated together with simple C(3)-sugar analogue (1-hydroxyacetone) or methylglyoxal. The formation of the corresponding vinylogous product, i.e. styrene, was measured under different moisture, pH, and temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…We also synthesized the 3,4-dihydroxy-styrene glucuronide, but it eluted earlier than M18. Nevertheless, the neutral loss of C 2 H 2 suggests that the deconjugated M18 is probably an isomer of dihydroxystyrene, most likely formed from the degradation of l -phenylalanine into styrene during the roasting procedure . Indeed, it has been shown that styrene can be aromatically hydroxylated by mouse liver microsomes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also synthesized the 3,4-dihydroxy-styrene glucuronide, but it eluted earlier than M18. Nevertheless, the neutral loss of C 2 H 2 suggests that the deconjugated M18 is probably an isomer of dihydroxystyrene, most likely formed from the degradation of l -phenylalanine into styrene during the roasting procedure . Indeed, it has been shown that styrene can be aromatically hydroxylated by mouse liver microsomes .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the neutral loss of C 2 H 2 suggests that the deconjugated M18 is probably an isomer of dihydroxystyrene, most likely formed from the degradation of L-phenylalanine into styrene during the roasting procedure. 38 Indeed, it has been shown that styrene can be aromatically hydroxylated by mouse liver microsomes. 39 The thermal degradation of Lphenylalanine to styrene, and its hydroxylation and further glucuronidation, can explain the presence of M18.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have demonstrated that the Maillard reaction under basically dry circumstances could result in release of the dangerous substances. Asparagine, glutamine, aspartic acid, and phenylalanine were developed for their potential to provide reactive intermediates, which have drawn special concern during the past few years. Nikolov and Yaylayan showed that lysine could transform into pent-4-ene-1-amine through a decarboxylative and deamination reaction when heated at high temperature. Subsequent intramolecular cyclization of pent-4-ene-1-amine provided piperidine, which could react with methyl transfer reagent to form mepiquat. ,, In essence, mepiquat arises from a Maillard-type reaction that requires free lysine, a reducing sugar, and an alkylating agent, heated under typically dry conditions. , Recent studies show that pipecolic acid (PipAc) gives a major push to the constitution of mepiquat.…”
Section: Introductionmentioning
confidence: 99%
“…Research over the past years has shown that Maillard reaction-type mechanisms under essentially dry conditions can lead to the formation of vinylogous compounds amongst which acrylamide, derived from the amino acid asparagine, has raised particular attention in the past years (Stadler, Blank, Varga, et al 2002;Zyzak et al 2003;Goldmann et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Other amino acids such as, for example, glutamine, aspartic acid and phenylalanine, have also been studied with regard to their potential to furnish reactive intermediates mostly under dry Maillard reaction conditions (Stadler et al 2003;Goldmann et al 2009). In a recent study, Nikolov and Yaylayan have shown that lysine, when subjected to high temperature, can be converted to pent-4-ene-1-amine in a decarboxylative deamination reaction analogous to that leading to acrylamide.…”
Section: Introductionmentioning
confidence: 99%